Taking Pause: A COVID-19 Student Reflection on Global Health Research Opportunities, Training, and Institutional Reform - Chu, Casey; Griffin, Gianna; Williams, Joseph L. (Frontiers in Sociology, 2022)
Restrictions to research due to COVID-19 have required global health researchers to factor public health measures into their work and discuss the most ethical means to pursue research under safety concerns and resource constraints. In parallel, global health research opportunities for students have also adapted to safety concerns and resource constraints. Some projects have been canceled or made remote, but inventively, domestic research opportunities have been created as alternatives for students to continue gaining global health learning competencies. Knowing the ethical challenges inherent in short-term student global health research and research in strained health systems, it is intriguing why these safer alternatives were not previously pervasive in global health education. This paper provides perspectives from students training at academic institutions in the US on how COVID-19 disrupted student research and what can be learned from the associated shifts in global health research. Additionally, the authors take this opportunity to advocate for academic institutions from high-income countries to reflect on long-standing global health research conventions that have been perpetuated and bolster training for students conducting global health research. The authors draw on their experiences, existing literature, and qualitative interviews with students who pursued global health research during COVID-19.